Hereditary Protein S Deficiency in Young Adults with Arterial Occlusive Disease - Allaart, C F; Aronson, D C; Ruys, Th; Rosendaal, F R; van Bockel, J H; Bertina, R M; Briët, E (Thrombosis and Haemostasis, 1990)
Protein S is the vitamin K dependent cofactor of activated protein C. It has an important role in the regulation of blood coagulation and fibrinolysis. Hereditary protein S deficiency is associated with familial venous thrombophilia. Since a few patients with arterial occlusions have been reported to be protein S deficient, it is speculated that hereditary protein S deficiency may be also a risk factor for the development of arterial thrombosis. In a group of 37 consecutive patients with arterial occlusive disease presenting before the age of 45, three patients were found heterozygous for hereditary protein S deficiency. None of the patients had a protein C deficiency or an antithrombin III deficiency. Family investigations showed a clear association between the hereditary deficiency and venous thrombosis, but a relation between the deficiency and arterial thrombosis was less obvious. A review of previous literature on patients with arterial thrombosis and protein S deficiency revealed that more extensive studies are needed to demonstrate whether or not hereditary protein S deficiency is a risk factor for the development of arterial thrombosis.